2015
DOI: 10.1002/aqc.2559
|View full text |Cite
|
Sign up to set email alerts
|

Mesohabitat associations of the threatened San Marcos salamander (Eurycea nana) across its geographic range

Abstract: Habitat loss is one of the most critical factors affecting the loss of species. However, habitat conservation of many threatened species is performed with incomplete information on habitat requirements and trophic ecology, thus presenting a challenge to designing and implementing recovery plans. The San Marcos salamander (Eurycea nana) is a federally threatened spring‐associated organism whose geographic distribution is limited to the headwaters of the San Marcos River in Texas, USA. Although its designated cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…While movement was frequent throughout the stream channel, overall abundances were highest near the spring outlet. This is consistent with previous observations for this and similar species ( Tupa & Davis, 1976 ; Sweet, 1982 ; Bowles, Sanders & Hansen, 2006 ; Pierce et al, 2010 ; Bendik et al, 2014 ; Diaz et al, 2015 ). However, the largest proportion of small juveniles was found 80 m downstream, at the limits of our study area and the subsequently updated critical habitat buffer ( US Fish and Wildlife Service, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…While movement was frequent throughout the stream channel, overall abundances were highest near the spring outlet. This is consistent with previous observations for this and similar species ( Tupa & Davis, 1976 ; Sweet, 1982 ; Bowles, Sanders & Hansen, 2006 ; Pierce et al, 2010 ; Bendik et al, 2014 ; Diaz et al, 2015 ). However, the largest proportion of small juveniles was found 80 m downstream, at the limits of our study area and the subsequently updated critical habitat buffer ( US Fish and Wildlife Service, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…Site occupancy within these stream reaches may also be predicted by other aspects of their habitat. Rock cover (RC) is an important habitat characteristic that is often correlated with presence and abundance of Eurycea ( Bowles, Sanders & Hansen, 2006 ; Pierce et al, 2010 ; Diaz et al, 2015 ). RC was measured as the mean of three visual estimates of the percentage of rocks available (i.e., unembedded) for cover (>8 mm) at the substrate surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these data suggest that small impoundments may play an important role in maintenance of stream salamander populations in an ecoregion characterized by ephemeral streams. This supports conclusions by others that habitat protection for salamanders is complex and requires attention to important habitats that are infrequently located and represent a small proportion of available habitat (Romano et al , ; Diaz et al , ).…”
Section: Discussionsupporting
confidence: 88%
“…Despite its low taxonomic resolution, findings from this study suggested a remarkable amount of diversity, with twelve separate orders reported from the gut contents of this one species of fish. This diversity was verified by a subsequent diet study of the San Marcos salamander, Eurycea nana Bishop whereby numerous taxa (also largely hard-bodied forms), were reported from the SMR for the first time (Diaz 2010). …”
Section: Introductionmentioning
confidence: 66%